Finite control set model predictive control scheme of four-switch three-phase rectifier with load current observer. (April 2018) - Tian, Lisi; Zhao, Jin; Zhou, Dehong
Abstract: Three-phase rectifier is typically realized by six power switches. However, this rectifier is fault sensitive in power switches. To enable continued controllable operation, the grid phase with fault rectifier leg can be connected to center tap of the dc-link capacitors, known as the four-switch three-phase rectifier (FSTPR), using hardware reconfiguration. However, the symmetry of three-phase currents and reliable operation of the FSTPR cannot be retained due to the offset of the two-capacitor voltages. This paper proposes a finite control set model predictive control (FCS-MPC) to obtain the balanced three-phase current with the offset of two-capacitor voltages suppressed. The PI-Controller-free FCS-MPC with a second-order Luenberger observer is adopted to improve the dynamic performance of FSTPR. The performance of the proposed control scheme is illustrated by extensive simulation and experimental results. The comparison with the conventional voltage-oriented-control, which is based on PI controller and pulse width modulation (PWM), is also presented to show the superiority of the proposed FCS-MPC. Highlights: Predictive control of four-switch rectifier with voltage offset suppressed. Load current observer is designed for four-switch three-phase rectifier. Better steady and dynamic performance than the conventional PI controller.